Bol' . Bol' . Pain . Боль - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interviews with the Belorussian writer Svetlana Aleksienko, who writes on acute social problems, and with the military pilot Aleksandr Sokolov, a participant of the Afghan war. Беседы с белорусской писательницей Светланой Алексиенко, пишущей на острые социальные темы, и c военным летчиком Александром Соколовым, участником войны в Афганистане.